Implementation of the online teacher competency improvement training program in the diklat.co semarang learning community - Haris Pribadi; Deni Hardianto (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
This study aimed to describe the process and impact of online teacher competency improvement training through the Diklat.co platform in supporting the implementation of the Kurikulum Merdeka (Freedom Curriculum). This research employed a qualitative approach with a case study method. The data were collected through observations, interviews, and documentation of the training implementation. The findings indicate that online-based training effectively enhances teachers’ pedagogical and professional competencies. This occurs through reflective discussions, sharing of best practices, and the use of technology in the learning process. The participants reported increased confidence in applying differentiated instruction and diagnostic assessments following the training. However, challenges remain, including limited infrastructure, varying levels of digital literacy, and scheduling constraints that overlap with teachers’ existing workloads. This study recommends the online-based training model as a flexible, collaborative, and relevant alternative to support teacher professionalism development in the digital era.